Relaxant Effect of trans-Resveratrol on Isolated Porcine Coronary Arteries - Jäger, Ulrich; Nguyen-Duong, Hoang (Arzneimittelforschung, 1999)
Recent studies provided evidence that trans-resveratrol (3,4’,5-trihydroxystilbene, found in high concentrations in some red wines, may possibly decrease the risk of coronary heart disease mortality. The aim of this study, performed with large epicardial porcine coronary arteries (PCA) strips, was to investigate the relaxant effect of trans-resveratrol on these main conductance vessels, which have been described to be pathologically prone for vasospastic contractions. The data show that the tonic component of the biphasic contractions induced by histamine, as well as the contractions induced by F- ions (10 mmol/l), which activate G proteins downstream of the receptors, could dose-dependently be inhibited by trans-resveratrol (0.1-100 The EC50 values of the dose-response curves established for the inhibition of the sustained component of histamine-induced contractions were very similar to those obtained for the relaxations of fluoride-induced contractions: 0.45 ± 0.08 and 0.29 ± 0.05 μmol/l, resp. (n = 6). Ouabain (10 μmol/l)-induced contractions and rhythmic contractions elicited by tetraethylammonium (12 mmol/l) were also strongly inhibited by trans-resveratrol (20 μmol/1). It may be inferred from the results obtained in this study, that the relaxation of the coronary conductance vessels induced by trans-resveratrol is possibly based on a nongenomic interaction with steroid-like receptors located on the cell membrane.
Keywords: trans-Resveratrol; 3,4’,5-Trihydroxystilbene, porcine coronary arteries, relaxant effects